Investigação da participação da quimiocina CXCL1 associada às células da glia na gênese da dor neuropática - Moraes, Thamyris Reis (2018)
Neuropathic pain is caused by injury or dysfunction of the somatosensory nervous system, affects between 6.9% and 10% of the world population and is related to decreased quality of life and sleep, besides patients do not respond to current treatments. Studies have shown that not only neurons play a role in the modulation of neuropathic pain, but glial cells play a key role in this process by releasing pro-inflammatory substances like chemokines, modulating the nociceptive process. Thus, the present study investigated the involvement of chemokine CXCL1 and glia cells, being microglia and astrocytes, in the genesis of neuropathic pain. Male Wistar rats weighing 250g to 300g were used. The Von Frey filaments apparatus was used to evaluate the nociceptive threshold and chronic constriction injury of the sciatic nerve (CCI) was used for the induction of neuropathic pain. To evaluate the expression of the microglia markers (Iba1), astrocytes (GFAP) and the chemokine CXCL1 the Western blot assay was used. Involvement of the CXCR2 receptors was investigated using the selective antagonist SB225002 and the participation of microglia and astrocytes was evaluated using the minocycline and fluorocitrate inhibitors, respectively. In addition, recombinant CXCL1 was administered i.t. to investigate the involvement of this chemokine in nociception. The results showed that the animals pretreated with SB225002 had decreased nociception, indicating the involvement of these receptors in neuropathic pain. In addition, recombinant CXCL1 was able to cause nociception at the spinal level and minocycline and fluorocitrate reduced mechanical allodynia caused by CXCL1 and CCI. There was an increase in CXCL1 chemokine expression in animals submitted to neuropathy induction, demonstrating its role in neuropathic pain. In the animals submitted to CCI there was an increase in the expression of the microglial marker Iba1, but not the GFAP astrocyte marker GFAP, and the CXCR2 antagonist was able to decrease the expression of the microglial markers and astrocytes in these animals. Thus, the present study suggests the presence of CXCR2 receptors in glia cells during neuropathic pain, as well as the involvement of CXCL1 chemokine in the genesis of this pain.